ANIMATION RECOGNITION OF THE ORIGIN OF THE YAA QOWIYYU TRADITION IN JATINOM (Arty: Jurnal Seni Rupa, 2021)
Abstract Yaa Qowiyyu is one of the most famous art festivals from Jatinom, Central Java. The festival, also known as the distribution of apem, is in great demand by residents around and outside the Jatinom area. Apem is a traditional food that is iconic every time this festival is held. Not a few people know the origin of how this Yaa Qowiyyu tradition was first carried out. One way to spread information about the origin of the Yaa Qowiyyu tradition is to use animated stories. This assignment focuses on creating characters in the Yaa Qowiyyu Time Traveler animated story which is made using animation principles. This assignment is made using Pre Production, Production and Post Production methodologies. The end result is a character who will be the main character in the animated story Yaa Qowiyyu Time Traveller.